Spent brewer yeast status in halal food industry: an analysis from shariah and science perspectives - Ramli, Siti Nur Hamizah (Rynnye Lyan Resources, 2022)
The yeast, Saccharomyces cerevisiae, is the protagonist in brewing, while spent brewer yeast is a by-product of beer production. Khamr or intoxicant, and its by-product, are prohibited by Shariah, whereas yeast is used to produce alcoholic beverages. Generally, the yeast dies after alcohol fermentation, but some of them settle at the bottom of the fermentation tank. Concerns arise about whether post-purification of spent brewer yeast will take place as it is initially considered impure (najs) because alcoholic fermentation occurs in yeast cytosol. This study examined spent brewer yeast’s halal status, investigated the formation of spent brewer yeast, and analyzed methods of legal ruling on spent brewer yeast according to Shariah and science perspectives. Qualitative approaches had been applied including library research, fiqh adaptation (al-takyif al-fiqhi), and content analysis. Istihalah (transformation), debittering, and decolourization have been proposed for purification. Study shows that spent brewer yeast colour changed from chocolate brown to cream-white after purification, but there is still no complete removal of bitterness from beer achieved. The study concludes that spent brewer yeast can be permissible (halal) for consumption if the colour, odour, and taste of the beer are completely purified from the spent brewer yeast.